Tradisi “Sapparan” Sebagai Bentuk Akulturasi Budaya Daerah dan Islam di Kabupaten Probolinggo - Herwati (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2022)
Abstract: Criticism of modernists who think negatively of the Selametan tradition, it is necessary that positive spiritual values ​​be re-appeared in the Selametan series and tradition. The